PERAN MANAJEMEN SUMBER DAYA MANUSIA DALAM PENINGKATAN KINERJA DI SDN GEDONG DALEM 03 KOTA CILEGON - Prasetyo, Eko; Yusuf, Furtasan Ali; Hayadi, B. Herawan; Rahmulyana, Anjar; Fatimah, Fatimah (Yayasan Education and Social Center, 2024)
This research aims to analyze the role of human resource management (HR) in improving performance at Gedong Dalem 03 State Elementary School (SDN), Cilegon City. This research uses a qualitative approach with a case study method to explore in-depth information about HR management practices implemented at the school. This research involved interviews with school administrators, teachers, and administrative staff to understand how HR management is implemented in basic education. In addition, analysis of documents such as HR policies, training programs and performance evaluations is also carried out to gain a comprehensive understanding. It is hoped that the results of this research will provide insight into the effectiveness of the role of HR management in improving performance at SDN Gedong Dalem 03, Cilegon City. The implications of the findings of this research can make a positive contribution to improving human resource management in basic education institutions and provide recommendations for improvement and development of better policies. Thus, it is hoped that this research can become a reference for related parties in improving the quality of education through optimizing human resource management